Benefits of Levonorgestrel Intrauterine Device Use vs. Oral or Transdermal Progesterone for Postmenopausal Women Using Estrogen Containing Hormone Therapy - Kaylee Clark; Sarah M. Westberg (University of Minnesota Libraries Publishing, 2019)
Background: Endometrial hyperplasia is a major concern for women that start estrogen replacement therapy (ERT) to control symptoms experienced during perimenopause and postmenopause.  Progesterone provides protection against endometrial hyperplasia, and there are multiple dosage forms of progesterone available.  Intrauterine progesterone may offer an appealing option with additional benefits beyond endometrial protection for patients. Objective: The overarching objective of this systematic review is to characterize the relationship between levonorgestrel containing intrauterine devices (LNG-IUD) and the prevention of endometrial hyperplasia in peri- and postmenopausal women. Specifically, this systematic review addresses whether LNG-IUD has equivalent efficacy of protecting against endometrial hyperplasia, but an improved safety profile when compared to oral progesterone in women using ERT. Methods: OVID Medline, Scopus, and Cochrane were used to find available studies that have investigated the relationship between endometrial hyperplasia prevention and varying dosage forms of progesterone. Randomized control studies comparing LNG-IUD with no treatment, placebo, or other hormonal therapy in adult females were included. In addition, due to a lack of randomized control studies, four non-comparative studies were included. Results: There were eleven total studies included that investigated LNG-IUD use in women on ERT. According to the studies, the LNG-IUD was equally effective as other routes (oral, vaginal) of progesterone administration in protecting against endometrial hyperplasia. Conclusions: The LNG-IUD prevents endometrial proliferation at least as effective as oral or vaginal forms of progesterone. LNG-IUD is a safe option for women starting estrogen replacement therapy and has added benefits due to decreased adverse effects.   Article Type: Student Project